Zhong in the analects with insights into loyalty - Sung, Winnie (University of Hawai‘i Press, 2021)
This chapter attempts to analyze the notion of zhong 忠 in the Analects. Since zhong is often translated as “loyalty” in the existing literature, it is tempting to read Confucius as placing emphasis on the importance of being loyal, and this will easily call to mind many negative connotations associated with loyalty such as blind submission, ungrounded favoritism, and the erosion of integrity. Such a strong association between zhong and loyalty might prevent us from fully understanding why zhong is valued. The aims of this chapter are to examine Confucius’ use of zhong as recorded in the Analects, to articulate the early Confucian conception of zhong, and to extract ethical insights from such an early Confucian conception by juxtaposing it against the contemporary conception of loyalty.